Unefficiency Settlement Of Fintech Lending Disputes And How Legal Framework To Settle It: Indonesia Perspective - GUMBIRA, SENO WIBOWO; PUSPITAWATI, DHIANA; TEJOMURTI, KUKUH (The journal of contemporary issues in business and government, 2021)
This article aims to analyze fintech lending dispute resolution's inefficiency and how the ideal concept is to realize the principle of user dispute resolution under the Financial Services Authority Regulation Number 77 / POJK.01 / 2016. The research method used is prescriptive normative legal research using primary and secondary legal materials. According to POJK 77 / POJK.01 / 2016, the results show that dispute resolution on the lending and borrowing services based on the information technology should be done quickly and cheaply. However, there is still no effective and efficient dispute resolution institution established in practice because fintech lending administrators in the standard e-contract clause directly determine one court, which may be very far from the parties' place (lender or borrower). Besides, there is no clear mechanism related to dispute resolution for Fintech Lending users, so Fintech Lending Organizers do not have different guidelines for resolving disputes that result in Fintech Lending Organizers. The complicated mechanism and complexity of resolving fintech lending disputes are not proportional to the loan value, which may be less than the dispute resolution process's cost. The Financial Services Authority must establish an online alternative Dispute Resolution Agency so that the parties can be effective and efficient in resolving disputes.